(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and Purpose: The human nose has been reported to differ in its anatomy and morphology between different racial and ethnic groups. Nasal anthropometric features when studied can provide useful information for reconstruction or esthetic surgical procedures and personal identification for forensic purposes. Method: A total of 311 subjects with age (19-23) years were divided according to gender, race (Arabic or Kurdish), and residence regions in Iraq (north, middle and south). Different nose parameters were measured for the subjects using digital Vernier caliper. Results: Comparing races, the nose height and nose length were significant between Arab and Kurds, nasal index showed (60, 60.6) for Arabic vs. Kurdish, respectively. Sexual dimorphism was significant in all the parameters obtained. The fine nose was the commonest among all subjects. Parameters analysis revealed high positive significant correlation among various parameters except the nasal index that showed negative correlation with nasal height and length. Conclusions: Nasal morphometric parameters were unique for each person and have variations between different race (Arabic and Kurdish), gender variation and the correlation among various parameters been recorded for Iraqi people. These morphometric evaluations are the key for standardization among Iraqis, and in comparison with different countries, this have great values in anatomical, surgical (aesthetic) and forensic aspects regarding personal identification.